Lipid Profile in Patients With Amyotrophic Lateral Sclerosis: A Systematic Review and Meta-Analysis - Liu, Jiao; Luo, Xiaoyue; Chen, Xueping; Shang, Huifang (Frontiers in Neurology, 2020)
Background: Studies have investigated the lipid profile in ALS, including the levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), higher low-density lipoprotein (LDL), and the associations with mortality of ALS, but the results were inconsistent. Therefore, we conducted this meta-analysis to systematically answer this unsolved question. Methods: We searched all the related studies that probed into the association between serum lipid levels and ALS based on PubMed, EMBASE and Cochrane library from inception through to February 2019. The quality of the included studies was evaluated by using Newcastle-Ottawa Scale (NOS). All the statistical analyses of this meta-analysis were performed using Stata version 12.0. Results: Fourteen studies with a total of 4386 ALS patients and 3938 controls were included. Among them, ten studies indicated that compared to the controls, ALS patients from both European and Asian had lower levels of TG and HDL; but the levels of TC and LDL were higher in ALS patients from European. However, after systemic analyses, the altered TC level was significant only in Asian ALS patients; the differences of other lipids were not significant. Analyses of four studies showed that the levels all lipids were not associated with overall mortality in ALS. Conclusion: The results of present study showed that Asian ALS patients had lower TC levels than controls, and levels of all the lipids were not associated with mortality of ALS.